Economic Policy Uncertainty and Family Firm Innovation: Evidence From Listed Companies in China - Qi, Yong; Dong, Shaoyu; Lyu, Simeng; Yang, Shuo (Frontiers in Psychology, 2022)
With the advancement of China's economic transformation, economic policies are becoming more and more uncertain. How does the economic policy uncertainty affect family firm's innovation decision-making? Which kind of family firms can better adapt to the changing market environment, and which kind of factors will enhance their innovation decision-making? The answers to these questions are of great practical significance for the continuous development of family businesses in a complex system environment. This study examines the relationship between economic policy uncertainty and innovation in China’s family firms. We provide evidence that economic policy uncertainty positively relates to family firm innovation. Moreover, the relationship is affected by factors such as directors’ executive background and access to state-owned equity. Further analysis indicates that economic policy uncertainty can promote family firms’ innovation activities by improving their risk-taking, internal capital market circulation, and reducing political connections.